Do trabalho na escola ao trabalho para e com a escola: as contribuições do assessor pedagógico, sob a ótica do professor, para a formação permanente em contexto de trabalho - Castello, Elaine Cristina (2023)
This Master's research has the general aim of identifying in the work of the pedagogical advisor the contributions to the continuing teacher´s education training in the work context, from the teachers´ view. As specific objectives: (1) to characterise the ongoing education training processes carried out by the advisor in the work context; (2) to identify the gaps in teachers' training based on their view and reflection on their own action; (3) to map the training strategies developed by the pedagogical advisor and (4) to build propositions for pedagogical advisors in a work context considering the teachers' contributions. The qualitative approach study based on Ludke and André (2018), was justified by the need for recognition of the professional role of pedagogical advisor, through his/her contributions in the continuing education training from the teachers´ view. The theoretical framework selected to support the research consisted of the conceptions of: Imbernón (1994, 2001, 2009, 2010, 2011), Garcia (1999, 2009), Nóvoa (1987,1991, 1995, 1998, 2000, 2010, 2013, 2022) and Tardif (1991, 2002, 2009, 2012). The research subjects were 83 teachers from all levels of education working in schools in the five regions of Brazil - North, South, Northeast, Southeast and Centre-west. The data collection was done through a questionnaire. The process of content analysis highlighted the importance of the pedagogical advisor as a trainer and his/her contributions to the continuing education of teachers. The methodologies used by pedagogical advisors are those considered relevant by teachers for in-service education training. This analysis pointed out the pedagogical advisor as an advanced peer of teachers who participate in the actions of the editorial service and that this research can contribute with proposals to qualify the education training plans developed by pedagogical advisors